“The system is a bit broken…” a qualitative exploration of barriers in the pathway for diagnosing Developmental Coordination Disorder - Lucy H. Eddy; Nat K. Merrick; Cara E. Staniforth; Jade L. Jukes; Liam J. B. Hill; Mark Mon-Williams; Farid Bardid; Rebecca Murray (PLoS ONE, 2026)
Background Approximately 5% of children are affected by a neurodevelopmental disorder of their sensorimotor skills. DSM-V and ICD-10, the two most widely used diagnostic systems, define this diagnostically as ‘Developmental Coordination Disorder’ (DCD) or ‘Specific Developmental Disorder of Motor Function’ (SDDMF), respectively. A diagnosis of DCD has been found to have a detrimental impact on a range of outcomes (e.g., health and education). It is therefore crucial that these children receive timely intervention. This is reliant, however, on effective assessment and support pathways. Research has shown there is great parental dissatisfaction, but there has been limited research exploring a clinical and education perspective. This study therefore aimed to understand barriers and facilitators for clinical and education practitioners in the pathway in a diverse district in the UK (Bradford). Methods Semi-structured interviews were completed with stakeholders across the pathway to identify barriers and facilitators to assessing, diagnosing, and supporting children with sensorimotor skill difficulties. Theoretical thematic analysis aligned to the Capability, Opportunity, Motivation model of Behaviour change (COM-B) was used to analyse the qualitative data. Results Interviews revealed many barriers in the DCD pathway related to capability (confusing terminology, inconsistent knowledge, inappropriate referrals), opportunity (resource constraints, DCD being considered low priority, and disconnected services), and motivation (overlapping job roles, a desire to consider those with difficulties not eligible for a diagnosis). No facilitators were consistently identified across interviews. Conclusion Families face multiple barriers to obtaining a diagnosis for their child through existing clinical pathways for assessment and support. These findings are unlikely to be unique to Bradford, due to international research highlighting these issues via parental interviews. These findings therefore may reflect challenges both nationally and internationally within DCD pathways. There is an urgent need for: (i) clear communication across different services (with consistency in terminology), and (ii) a more collaborative and integrated approach to assessment, diagnosis, and support in order to help these children thrive.